2009
DOI: 10.1021/jp9061797
|View full text |Cite
|
Sign up to set email alerts
|

Reduced and n-Type Doped TiO2: Nature of Ti3+ Species

Abstract: Defect states in reduced and n-type doped titania are of fundamental importance in several technologically important applications. Still, the exact nature of these states, often referred to as “Ti3+ centers”, is largely unclear and a matter of debate. The problem is complicated by the fact that electronic structure calculations based on density functional theory (DFT) in the local density approximation (LDA) or semilocal generalized gradient approximation (GGA) provide results that do not account for many of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
714
1
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(779 citation statements)
references
References 76 publications
52
714
1
12
Order By: Relevance
“…DFT+U has proved to be appropriate to describe Nb anatase doping. [63][64][65] As for the present work, it is crucial to understand how the N and Nb codopants . [63][64][65][66][67][68] The picture becomes quite different when both N and Nb are simultaneously added to the anatase lattice ( Figure 5).…”
Section: Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…DFT+U has proved to be appropriate to describe Nb anatase doping. [63][64][65] As for the present work, it is crucial to understand how the N and Nb codopants . [63][64][65][66][67][68] The picture becomes quite different when both N and Nb are simultaneously added to the anatase lattice ( Figure 5).…”
Section: Electronic Structurementioning
confidence: 99%
“…[63][64][65] As for the present work, it is crucial to understand how the N and Nb codopants . [63][64][65][66][67][68] The picture becomes quite different when both N and Nb are simultaneously added to the anatase lattice ( Figure 5). As already calculated for N doping 9,69 , valence nitrogen states lie in the proximity of the valence band (VB).…”
Section: Electronic Structurementioning
confidence: 99%
“…These defects are, however, more difficult to characterize. 62 It has been shown that both surface BBOv's [47][48][49]51,52,56,63,64 and subsurface defects [63][64][65][66][67][68][69][70][71][72] are capable of affecting the chemistry on the TiO 2 (110) surface.…”
Section: Photocatalysis Of Methanol On Tio 2 (110)mentioning
confidence: 99%
“…The description of reduced rutile has been an active topic for many years, with much discussion as to whether the dominant species involved are Ti interstitials 15 or oxygen vacancies. 18 Both defects can produce the same signature in ultraviolet photoemission spectroscopy and in density functional theory (DFT) simulations, 19 i.e. reduced Ti 3+ ions.…”
Section: Introductionmentioning
confidence: 96%